Pengaruh Penerapan Sistem Akuntansi Keuangan Daerah (SAKD) Terhadap Akuntabilitas Laporan Keuangan - Novarina, Dian Nadya; Rahayu, Dwi; Rohayati, Iis (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Implementation of Regional Financial Accounting System is supporting the creation of financial management that is fair, transparent, and accountable in order to result in financial information that can be used as a basis for decision making. The purpose of this study to obtain empirical evidence on the Application of the Regional Financial Accounting System for Financial Statements Accountability in Local Government. The research method used is explanatory, where research aims to explain the position of the variables studied and the causal relationship between variables with one another through hypothesis testing. Data collection through field research using questionnaires and research literature. The results showed that the application of financial accounting system in Government Bandung area is adequate and accountability in the financial statements of the Government of Bandung can be said to be good. From the analysis conducted can be concluded that the adoption of the area of ​​financial accounting systems and financial statements at the Government Accountability Bandung has been implemented properly and adequately. Partially Implementation of Regional Financial Accounting System effect Against Accountability Financial Statements and have a strong relationship. Local government needs to evaluate and improve the use of local financial accounting systems in order to improve the quality of supervision and can provide the financial information required by the user accountable financial statement information.